Gunnison Basin climate change vulnerability assessment: for the Gunnison Climate Working Group - Neely, Betsy, editor; Rondeau, Renée Jane, editor; Sanderson, John, editor; Pague, Chris, editor; Kuhn, Bernadette, editor; Siemers, Jeremy, editor; Grunau, Lee, editor; Robertson, J., editor; McCarthy, P., editor; Barsugli, J., editor; Schulz, T., editor; Knapp, C., editor; et al. (Colorado State University. Libraries, 2011)
This report summarizes the results of a landscape-scale climate change vulnerability assessment of the Upper Gunnison Basin (above Blue Mesa Reservoir; referred to as Gunnison Basin in this report) to determine the relative vulnerability of 24 ecosystems and 73 species of conservation concern, using methods developed by Manomet Center for Conservation Science and NatureServe. The report also summarizes the results of a social vulnerability and resilience assessment of ranching and recreation sectors in the Basin.
December 31, 2011.
Keywords: ecosystems; climate change; Colorado; ecological impact